Impacts of engine lubrication oil-derived ash on soot oxidative reactivity on a catalytic gasoline particulate filter. (May 2022) - Bock, Noah R.H.; Kittelson, David B.; Northrop, William F.
Abstract: Characterizing soot oxidation kinetics is crucial for understanding how gasoline particulate filters (GPFs) perform both in terms of filtration efficiency and pressure drop. The most common method for measuring soot oxidative reactivity is thermogravimetric analysis (TGA). Because TGA is an offline method, it may inaccurately predict how soot oxidizes on a GPF, especially if a catalytic washcoat is present that may enhance oxidation rates through surface interactions as the soot loads on the filter. In this work, a novel in-situ soot oxidative reactivity measurement method was developed. The method involved loading a catalytic GPF under high temperature conditions conducive to soot oxidation and measuring the filtration efficiency of 100 nm particles. A correlation was made between filtration efficiency and loaded soot mass on the filter to allow calculation of the soot oxidation rate. The method was evaluated in experiments using a 2.0 L gasoline direct injection (GDI) engine with three oils of varying additive packages, including an oil with a high zinc dialkyldithiophosphate (ZDDP) concentration, a non-additive, pure poly-alpha olefin (PAO) oil, and an oil with a high concentration of calcium sulfonate. Calculated specific soot oxidation rates ranged from ∼0.06–0.6 min −1 and showed strong dependence on GPF inlet gas temperature and lubrication oil additive type. The results clearly demonstrated a catalytic effect of calcium-containing ash particles. Reactivity of soot produced by the engine running with the high calcium containing lubrication oil was increased. Similarly, the results indicated that the catalytic washcoat on the filter increased soot oxidation rates on-filter, especially at low soot loading. Conversely, the ZDDP oil additive exhibited a reactivity inhibiting effect, resulting in lower soot oxidation rates. This work represents the first known in-situ soot oxidative reactivity measurements on a GPF and elucidates the effect of lubrication oil additives and catalytic washcoat on oxidation rate. Highlights: In-situ oxidative reactivity measurements show impact of lubrication oil additives. Catalyst-coated particulate filter increases soot oxidation rate at low soot loading. Calcium containing ash particles increases soot reactivity through catalytic action. Zinc dialkyldithiophosphate oil additive inhibited soot reactivity.